KONSEP PENDIDIKAN SUFISTIK MENURUT IBNU ATHAILLAH AS-SAKANDARI DALAM KITAB AL-HIKAM AL-ATHAIYYAH DAN RELEVANSINYA TERHADAP PSIKOLOGI PENDIDIKAN ISLAM - Jannah, Eka Miftachul; Kholid, Abdul; Waqfin, Mohammad Saat Ibnu (JoEMS (Journal of Education and Management Studies), 2021)
The world of Islamic education is currently experiencing various problems, such as decreasing morale and character of students, unharmonious relationships between various elements in educational institutions, decreasing interest and learning motivation of students, and incompatibility of teaching materials with the mental development of students. Seeing this, various offers emerged to understand and solve various problems related to Islamic education, namely through the psychology of Islamic education. There are also alternative offers, namely through Sufistic education or Sufism-based education. Then, among the many Islamic Sufi thinkers, Ibn Athaillah as-Sakandari is one of the phenomenal thinkers and practitioners of Sufism. One of his works, the book al-Hikam al-Athaiyyah, contains wisdom stories that have been chanted by several scholars of Sufism. Departing from this, this research aims to describe and analyze Ibn Athaillah's thoughts on Sufistic education in his work, the book al-Hikam al-Athaiyyah and to explain and analyze the relevance of Ibn Athaillah's thoughts on sufistic education in his work, the book al-Hikam al- Athaiyyah with the psychology of Islamic education.